Inclusión financiera a través de la bancarización y soluciones crediticias para microempresas por parte de la banca pública costarricense: el caso de Grupo Empresarial ME en Liberia, Guanacaste - Martínez Solís, Arnoldo José (2023)
Today's globalized world demands the creation of easy access to bank accounts and financing. Therefore, new financial inclusion trends are emerging, made up of different solutions on banking and credit issues. The offer is wide and varies between banks. It is necessary to point out that the Costa Rican financial system is made up of different entities, amount of this entities, stands out the private banks, banks created by special laws and the state commercial banks, which play an essential role in promoting the development and growth of the country. Banco de Costa Rica and Banco Nacional de Costa Rica are institutions that represent the state banking of the country; which have the obligation to create products and services that promote financial inclusion. Therefore, they make bank accounts and facilities available to the population for capturing resources as a pillar for channeling savings and investments. They also give credit solution support to companies for their evolution; this includes micro-enterprises who require funds to satisfy different investment plans. Another scenario, in Costa Rica there are different modalities for the exercise of productive and commercial activities. Which is why they are found in a business park: from corporations to limited liability companies under legal figures among the most common; same way, this type of activities are carried out on a personal basis. Business groups made up of two or more micro-enterprises, with various activities that complement and diversify the national economic activity, are also identified. It is important to mention that small companies contribute to the economic activation of the country with the creation of jobs, goods, products and services that satisfy the needs and consumption of families. This allows analyzing their importance in the economic cycle; therefore studying the financial inclusion offered by Costa Rican public banks to microenterprises is the main purpose of this research. It is important for the investigation the participation of SME executives from state-owned banks and the business group Me which is made up of the micro-enterprises CRME Sociedad Anónima; 3102 514803 Sociedad de Responsabilidad Limitada; Avenida Diecinueve Sociedad Anónima and RDYR Sociedad Anónima. Each of them dedicated to different commercial activities that complement its operations at the service of the Liberian population and surrounding areas. It is necessary to point out that the operations of the Me business group require bankarization and access to credit for the multiple transactions that its operations requires from which the management of payments, savings and investment, among others, are derived. It is because of what mentioned above that an investigation structured in four chapters is presented. The first shows background, justification, explains the problem and sets out the objectives of the study. The second chapter exposes the conceptual framework with the most elementary definitions that help to understand the research and shows a methodological framework that details the approach applied for the development of each section. The third chapter contains the analysis and interpretation of the results of the information collected in the investigative process and data generated with the application of interviews to the research subjects. Finally, chapter four reveals the conclusions and recommendations reached by the researcher with the study developed.